Effect of Flavourzyme on proteolysis, antioxidant activity and sensory qualities of Cantonese bacon. (15th December 2017) - Zhang, Siyu; Zhang, Chaoyang; Qiao, Yan; Xing, Lujuan; Kang, Dacheng; Khan, Iftikhar Ali; Huang, Ming; Zhou, Guanghong
Highlights: The Cantonese bacon was obtained from black-breed pigs and added by Flavourzyme at different levels. Flavourzyme addition accelerated the proteolysis of Cantonese bacon. Flavourzyme addition improved the antioxidant activity and eating attributes of Cantonese bacon. Abstract: The aim of this study was to investigate the influence of Flavourzyme on protein degradation, antioxidant activity and sensory qualities of Cantonese bacon made at 60 °C for 28 h. Flavourzyme was used at doses of 8, 16, 24, 32 and 40 LAUP/kg of raw meat. Results indicated that Flavourzyme addition in Cantonese bacon promoted proteolysis, which was reflected by the increase of various free amino acids and SDS-PAGE-detected changes in the myogen and myofibrillar proteins. Sensory qualities were improved while TPA (texture profile analysis) was decreased significantly ( P  < 0.05). The best sensory scores were obtained at between 24 and 32 LAPU/kg. Besides, Flavourzyme addition improved antioxidant activity, and decreased water activity and protein carbonyl content of Cantonese bacon. This study indicated that the addition of Flavourzyme improved eating attributes and storage stability of Cantonese bacon.